On the Behavior of the Solution of the Wave Equation - Hendra Gunawan; Wono Setya Budhi (Jurnal Matematika & Sains, 2004)
We shall here study some properties of the Laplace operator through its imaginary powers, and apply the results to understand the behavior of the solution of the wave equation.